Genome drafting of nosocomial infection CRE Klebsiella pneumoniae confirming resistance to colistin and eravacycline, carrying blaNDM-1, mcr-1, and blaKPC-2, in neonatology from November to December 2023 - Zhou, Xinlong; Wagh, Kailash; Lv, Guizhen; Sharma, Devender; Lei, Wei (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundCarbapenem-resistant Klebsiella pneumoniae (CRKP) is a critical pathogen in healthcare settings, associated with high mortality due to its extensive antibiotic resistance. In this study, we report an outbreak of CRKP in a neonatal intensive care unit (NICU) within a 200-bed tertiary hospital. The main goal of this study was to characterize the phenotypic and genomic profiles of the CRKP isolates involved in the outbreak and to gain insights into their resistance mechanisms and transmission dynamics within the NICU.MethodsThe study was conducted between November and December 2023 in a 5-bed NICU. Monthly surveillance cultures were performed to monitor colonization and infection with multidrug-resistant organisms. CRKP isolates were obtained from blood and nasal swabs of affected neonates. Identification and antimicrobial susceptibility testing were initially conducted using the Vitek®2 system with an N-395 card and further confirmed by 16S rRNA sequencing. Whole-genome sequencing (WGS) and antimicrobial resistance (AMR) profiling were performed to identify resistance genes and virulence factors. For genetic analysis, both Illumina short-read and Nanopore long-read sequencing were used, followed by hybrid assembly for enhanced genome resolution. Plasmid and resistance gene profiles were determined using AMRFinder and PlasmidFinder databases.ResultsA total of three CRKP isolates (designated Kp1, Kp2, and Kp3) were identified. Kp1 and Kp2 belonged to sequence type (ST) ST23 and were genetically near-identical, differing by a single allele, while Kp3 was of a distinct sequence type, ST2096, with 245 allelic differences from Kp1 and Kp2. All isolates were resistant to colistin and carried resistance genes, including mcr-1 and blaNDM-1,blaKPC2 confirming carbapenem resistance. Efflux pump genes and aminoglycoside resistance genes were also detected, providing a multifaceted defence against antibiotics. Plasmid analysis identified several incompatibility groups (IncFI, IncHI, IncFIB, IncX), indicating the potential for horizontal gene transfer of resistance determinants.ConclusionThis study highlights the complexity of CRKP outbreaks in neonatal care, with isolates exhibiting resistance mechanisms that complicate treatment. The plasmid profiles suggest these strains are reservoirs for multidrug-resistant genes, emphasizing the need for strict infection control and ongoing genomic surveillance. For neonatal care, these resistance challenges increase the risk of treatment failures and mortality, underscoring the importance of enhanced infection prevention and novel therapeutic strategies.